2019
DOI: 10.1002/aur.2202
|View full text |Cite
|
Sign up to set email alerts
|

Visual and Proprioceptive Influences on Tactile Spatial Processing in Adults with Autism Spectrum Disorders

Abstract: Children with autism spectrum disorders (ASDs) often exhibit altered representations of the external world. Consistently, when localizing touch, children with ASDs were less influenced than their peers by changes of the stimulated limb's location in external space [Wada et al., Scientific Reports 2015, 4(1), 5985]. However, given the protracted development of an external‐spatial dominance in tactile processing in typically developing children, this difference might reflect a developmental delay rather than a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 57 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…This may well explain the mixed reports of predictive coding in autism. Individuals with ASD can acquire appropriate priors from one-shot learning [29], prior trials [30], or statistically global settings [31,32,34,36]. That the priors are typically intact is also evidenced by the present finding that the ASD group of participants did not differ in their local prior updating from the TD group.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…This may well explain the mixed reports of predictive coding in autism. Individuals with ASD can acquire appropriate priors from one-shot learning [29], prior trials [30], or statistically global settings [31,32,34,36]. That the priors are typically intact is also evidenced by the present finding that the ASD group of participants did not differ in their local prior updating from the TD group.…”
Section: Discussionsupporting
confidence: 63%
“…Our finding that individuals with ASD show intact short-term updating but slow updating of the longer-term prior may well be consistent with the mixed reports of predictive coding in autism. Individuals with ASD can acquire appropriate priors from one-shot learning [32], prior trials [33], or statistically global settings [34,35,41]. In those studies, however, the volatility of the environment and the prior were often fixed throughout the test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent longitudinal study that investigated midline crossing behaviours showed that at 10 months of age (but not at five and 14 months), infants at risk of ASD or ADHD produced fewer manual actions that involved their hand crossing the body midline into the contralateral side of space compared to low-risk infants [86]. This reduced level of midline crossing may play a role in the recently demonstrated delay in the ability to represent touch across body postures in children with ASD [87,88]. Individuals with ASD also demonstrate hypoand/or hypersensitivity to individual sensory channels [89] and show disrupted multisensory integration processes [90].…”
Section: Discussionmentioning
confidence: 97%
“…These children may show little or no response to sensory stimulation (Randell et al, 2019) or show heightened response to touch (Espenhahn et al, 2021). In addition, they have an impaired ability to localize or discriminate tactile stimulation problems (He et al, 2021;Hense et al, 2019), especially when in presence of another sensory stimulation such as visual distractors (Poole, 2018). Despite significant deficits in processing tactile information, there is a considerable lack of research understanding the contribution of impaired tactile sensation especially in the foot to balance deficits in ASD.…”
mentioning
confidence: 99%